Two Unsuccessful Objections to the Apologetic Worth of Miracles - Larmer, Robert A. (Studia Philosophiae Christianae, 2025)
In this article I examine two common, widely used, objections to the apologetic worth of miracles and argue that they are unsuccessful. These are: (1) the objection that it would take an inordinate amount of evidence to establish the occurrence of certain events such as the Resurrection of Jesus, and (2) the objection that even if such events could justifiably be held to have occurred, it would be more rational to attribute them to unknown natural causes rather than supernatural intervention. Using the views of David Basinger, found in his 2018 Cambridge Elements monograph Miracles, as a foil, I argue that both objections are mistaken. —————————————- Zgłoszono: 12/05/2025. Zrecenzowano: 15/10/2025. Zaakceptowano do publikacji: 18/11/2025.